Simple and Controlled Method to Avoid Hyperperfusion of the Right Arm Following Axillary Artery Cannulation for Extracorporeal Membrane Oxygenator Support - Papadopoulos, Nestoras; Ahmad, Ali El-Sayed; Marinos, Spiros; Moritz, Anton; Zierer, Andreas (The Thoracic and Cardiovascular Surgeon, 2013)
The right axillary artery has become the cannulation site of choice for establishment of extracorporeal membrane oxygenator support in many centers. Dissection and cannulation of this vessel are simple and safe in the majority of patients. Typically, a side graft is used to avoid malperfusion of the right arm. Although this protocol offers many advantages, a common complication is the critical hyperperfusion of the right arm. Subsequent compartment syndrome and decline of antegrade inflow of oxygenated blood, especially into the brain and coronary arteries, can be life threatening in such critical patients. We describe herein a simple yet effective and controlled technique to avoid this particular problem.
Keywords: extracorporeal membrane oxygenation; outcomes (includes mortality, morbidity); surgery; complications